Vegetable oil-based polymers properties, processing and applications - Karak, Niranjan (Woodhead Publishing in materials., 2012)
The growing need to find a sustainable, environmentally-friendly replacement for petroleum-based materials is fuelling the development of bio-based polymers from renewable resources. Amongst the most promising of these are vegetable oil-based polymeric materials. Vegetable oil-based polymers provides a comprehensive review of the research in this important field. After an introduction to classification and polymerization, Vegetable oil-based polymers goes on to review the factors involved in polymer biodegradation. The extraction, purification and application of vegetable oils are then explored, along with vegetable oil-based polyesters and poly(ester amide)s, polyurethanes and epoxies. The book then reviews polyamides, polyolefins and vegetable oil-based hyperbranched polymers. It concludes with an analysis of vegetable oil-based polymer composites and polymer nanocomposites. Vegetable oil-based polymers is an indispensable guide for all those involved in the research and development of biopolymers as well as the wide range of industries looking for more sustainable polymer materials. Provides a comprehensive review of recent research in the area of vegetable oil-based polymeric materialsDiscusses vegetable oils and their derivatives, biodegradable polymers and the fundamentals of polymersExplores the extraction, purification and application of vegetable oils, along with vegetable oil-based polyesters and poly(ester amide)s, polyurethanes and epoxies.